2014
DOI: 10.3109/0886022x.2014.926755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatine and pioglitazone on Hk-2 cell line cisplatin nephrotoxicity

Abstract: Cisplatin is a chemotherapeutic agent, which is used in the treatment of various solid organ cancers, and its main dose limiting side effect of cisplatin is nephrotoxicity. The aim of this study is to investigate the role of pioglitazone and creatine on cisplatin nephrotoxicity in vitro. Real-time cell analyzer system (RTCA) was used for real-time and time-dependent analysis of the cellular response of HK-2 cells following incubation with cisplatin and combination with creatine or pioglitazone hydrochloride. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Our previous study reported that IC 50 of imatinib in SQUU-A cells calculated by RTCA system and WST-8 assay were 4 µM and 60 µM, respectively (sensitivity of 15 times) (6,7). Other research groups reported that IC 50 of cisplatin in HK-2 cells calculated by RTCA system and WST-8 assay were 0.76 µM and 25 µM, respectively (sensitivity of 33 times) (30,31). These previous data supported our data to show validity.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study reported that IC 50 of imatinib in SQUU-A cells calculated by RTCA system and WST-8 assay were 4 µM and 60 µM, respectively (sensitivity of 15 times) (6,7). Other research groups reported that IC 50 of cisplatin in HK-2 cells calculated by RTCA system and WST-8 assay were 0.76 µM and 25 µM, respectively (sensitivity of 33 times) (30,31). These previous data supported our data to show validity.…”
Section: Discussionsupporting
confidence: 91%
“…Pioglitazone, along its ability of suppress oxidative stress and damage through improving antioxidant capacity, has been reported to have a role in suppression of MAPK, Nf-kB signaling pathways and inhibition of TNFα with an IC 50 dose of 1.61 M at 24th hour and 2.85 M at 48th hour [14,15]. In order to evaluate the anti-proliferative effect of pioglitazone as single agents, we used several human non small lung cancer (NSCLC) cell lines: A549, H1299, H460, H1975, HCC827 and human bronchial epithelial cells, Beas2B, as control.…”
Section: Effect Of Pioglitazone On Proliferation Migration and Apoptmentioning
confidence: 99%
“…Based on these outcomes, HK-2 cells have been used for nephrotoxicity in vitro testing of a variety of compounds, i.e. heavy metals (Bao et al 2013, Fujiki et al 2014), endotoxin (Quoilin et al 2012, Wang et al 2015, commonly used toxic chemicals like cisplatin, polymyxin and cyclosporine A (Genc et al 2014, Keirstead et al 2014, Vizza et al 2013 and also for characterization of oxidative stress after H 2 O 2 treatment (Lee et al 2013, Lin et al 2014. These experiments showed that HK-2 cells are substantially rather sensitive to oxidative damage and that is why this cell line has been predominantly accepted as a suitable in vitro model for studying nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%